The pneumococcal bacteriocin streptococcin B is produced as part of the early competence cascade and promotes intraspecies competition - J. D. Richardson; Emily Guo; Ryan M. Wyllie; Paul Jensen; Suzanne Dawid (mBio)
ABSTRACT Streptococcus pneumoniae is an important human pathogen that normally resides in the human nasopharynx. Competence-mediated bacteriocin expression by S. pneumoniae plays a major role in both the establishment and persistence of colonization on this polymicrobial surface. Over 20 distinct bacteriocin loci have been identified in pneumococcal genomes, but only a small number have been characterized phenotypically. In this work, we demonstrate that three-fourths of S. pneumoniae strains contain a highly conserved scb locus that encodes an active lactococcin 972-like bacteriocin called streptococcin B. In these backgrounds, the scbABC locus is part of the early competence cascade due to a ComE binding site in the promoter region. Streptococcin B producing strains target both members of the population that have failed to activate competence and the 25% of the population that carry a naturally occurring deletion of the ComE binding site and the functional bacteriocin gene. The ComR-type regulator found directly upstream of the scb locus in S. pneumoniae strains can activate scb expression independent of the presence of the ComE binding site but only when stimulated by a peptide that is encoded in the scb locus of Streptococcus pseudopneumoniae, a closely related bacterium that also inhabits the human nasopharynx. Given the co-regulation with competence and the phenotypic confirmation of activity, streptococcin B represents a previously unrecognized fratricide effector that gives producing strains an additional advantage over the naturally occurring deleted strains during colonization.IMPORTANCEStreptococcus pneumoniae is a common cause of pneumonia, meningitis, sinusitis, and otitis media. In order to successfully colonize humans, a prerequisite to the development of invasive disease, S. pneumoniae must compete with other bacterial inhabitants of the nasal surface for space and nutrients. Bacteriocins are small antimicrobial peptides produced by bacteria that typically target neighboring bacteria by disruption of the cell surface. S. pnuemoniae encodes a large number of potential bacteriocin, but, for most, their role in competitive interactions has not been defined. This work demonstrates that isolates that produce the bacteriocin streptococcin B have an advantage over non-producers. These observations contribute to our understanding of the competitive interactions that precede the development of S. pneumoniae disease.